2017
DOI: 10.1007/s41207-017-0030-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous adsorption behavior of heavy metals onto microporous olive stones activated carbon: analysis of metal interactions

Abstract: The present work reports the synergistic and inhibitory adsorption effects involved in the multicomponent adsorption of heavy metal ions (Cu(II), Ni(II), and Cd(II)) from binary systems using chemically olive stone activated carbon (COSAC) as adsorbent. In order to evaluate the adsorption capacity of COSAC to remove studied heavy metals, adsorption of metal ions in single and binary systems were conducted. Kinetics adsorption rates in binary systems are very fast as compared to that in single ones and well rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 47 publications
(56 reference statements)
2
14
0
Order By: Relevance
“…These data are in accordance with the data obtained by other authors, and it can be concluded that higher molecular weight metals are removed much more than are lower molecular weight metals. 17,18 Ritchie's model assumes that the total reaction rate is controlled by the rate of ion exchange, and that the ion exchange is a second order reaction, i.e., in this case, the exchange itself took place by exchanging two ions of sodium from the zeolite with one ion of divalent metal from the solution. The Weber-Morris model was used to test whether the diffusion process defines the overall rate of reaction.…”
Section: Kinetic Modelsmentioning
confidence: 99%
“…These data are in accordance with the data obtained by other authors, and it can be concluded that higher molecular weight metals are removed much more than are lower molecular weight metals. 17,18 Ritchie's model assumes that the total reaction rate is controlled by the rate of ion exchange, and that the ion exchange is a second order reaction, i.e., in this case, the exchange itself took place by exchanging two ions of sodium from the zeolite with one ion of divalent metal from the solution. The Weber-Morris model was used to test whether the diffusion process defines the overall rate of reaction.…”
Section: Kinetic Modelsmentioning
confidence: 99%
“…The adsorbent adsorbs the copper, nickel and cadmium ions. The Langmuir and Sips model fitted for the mono-solute adsorption isotherms [47].…”
Section: Freundlich Isothermit Was An Empirical Expression Thatmentioning
confidence: 99%
“…antagonistic effect plays a significant role [39][40][41]. The total percent removal (% ) for the combined and individual system was obtained using…”
Section: The Interaction Effect Of the Pollutants In The Solution (Simentioning
confidence: 99%